Performance evaluation of the properties of gel patches based on the cross-linking reaction of partially neutralized sodium polyacrylate - Zhaoying Qi; Enzhao Wang; Yuzhou Cao; Rongshuang Tang; Jiquan Zhang; Jing Wu; Dawei Hao; Minchen Liu (PLoS ONE, 2026)
Four types of partially neutralized sodium polyacrylate (PNSP) were prepared using two commonly used neutralization degrees of sodium acrylate/acrylic acid in molar ratios of 50/50 and 35/65. The performance and rheological properties of these four gel patches were analyzed through quality evaluation and rheological assessment. Concurrently, the structure and performance of the four gel patches were discussed based on electronic nose testing, cryo-scanning electron microscopy (cryo-SEM), and thermogravimetry-mass spectrometry coupling analysis (TGA-MS). The results indicated that no significant changes occurred in the quality or rheological properties of the four gel patches over a 30-day period. Electronic nose testing, cryo-SEM, and TGA-MS results indicated that PNSP with equivalent neutralization levels had no significant impact on the mass, formulation characteristics, or structure of the gel patches.